Modern threats to information and communication systems and methods of protection against them - Peliukh, O.I.; Yesina, M.V.; Holubnychyi, D.Yu. (Radiotekhnika, 2024)
In the modern world, information and communication systems (ICS) have become an integral part of our lives, processing, storing and transmitting information. However, this dependence makes them extremely vulnerable to various threats. The article examines the current threats that call into question the normal functioning of ICS. The authors emphasise the constant evolution of these threats, which makes them more complex and dangerous. This necessitates constant research and development of new methods and means of information protection, as well as raising awareness of ICS users about cyber threats. The purpose of the article is to study modern ICS threats and develop recommendations for improving the level of information security (IS). The article provides a classification of ICS IS threats by various criteria: by the basic principles of the cybersecurity triad (confidentiality, integrity and availability), by sources of threats (internal and external), by the amount of damage caused (from general to private), by the degree of impact (passive and active) and by the nature of occurrence (natural and artificial). The article reveals the sources of threats to ICS security: unintentional (related to user errors, software failures or hardware failures) and intentional (cyber-attacks aimed at causing damage to ICS). Particular attention is paid to cyberattacks that are becoming more widespread. The authors describe different types of cyberattacks, as well as methods and means of their implementation. An important aspect of the article is the development of recommendations for improving the level of security. Along with the technical aspects of protection, the article considers the importance of implementing organisational measures such as security policy, access control and privilege management. The article also draws attention to the importance of complying with international and national standards for the protection of information in ICS. These measures help to avoid leakage or prevent unauthorised access to valuable information.